Determinants of the quality of life in the communes of the Poznań Agglomeration: A quantitative approach - Mizgajski, Andrzej; Walaszek, Marzena; Kaczmarek, Tomasz (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2014)
Since the 1990s, large urban agglomerations in the countries of Central and Eastern Europe have shown highly dynamic functional and spatial changes resulting from the transformation of their political systems. The aim of this study is to present differences in social, economic and environmental living conditions among the communes of a single agglomeration. This, in turn, allows a discussion, in the first place, of local factors, assuming that national and regional conditions in a given area are uniform. The study focused on the agglomeration of Poznań, which consists of the city of Poznań and 17 surrounding communes (Polish: gmina) forming the district, or ‘poviat’ (Polish: powiat) of Poznań. The analysis of variations in living conditions uses a set of nine indicators reflecting the local level of development in social, economic and environmental terms. The results lead to the conclusion that the development of urbanisation processes in suburban areas over the past 20 years has had a significant share in improving the living conditions of their inhabitants. In some communes they are, in fact, better than in the central city of Poznań.
Keywords: quality of life; Poznań agglomeration; sustainable development